Hubungan Karakteristik Terhadap Kecemasan Pemberian Air Susu Ibu di UPT Puskesmas Sulili Kabupaten Pinrang - Hamdiyah; Reski Devi Akib; Nur Laela; St. Nurbaya (Yayasan Literasi Sains Indonesia, 2022)
Anxiety can affect bodily functions, including the production of breast milk for nursing mothers. To find out whether there is a relationship between the characteristics of the anxiety level of breastfeeding in the UPT Puskesmas Sulili, Pinrang Regency is the purpose of this study. The research method uses the type of research used is